Revitalizing Rural Tourism: Local Economic Revival Through Community-Based Tourism Models - Olasoji, Timilehin (Politeknik Siber Cerdika Internasional, 2024)
Tourist rural play a role important in strengthening economy local, especially in areas rich in culture and nature However not enough develop in a way economy. In this context, the tourism model based on community (CBT) emerged as approach strategic to revitalize sector tourist rural with involving public local in management, so that impact the economy can be enjoyed directly by the community local. This study aims to evaluate the effectiveness of the CBT model in improving economy rural areas and improve involvement community local. Using approach qualitative descriptive, data collected through interview in-depth and observation participatory in some village tourism in Indonesia that has implementing the CBT model. The results of the study showed that CBT is capable increase income community, strengthening independence economy, and maintain sustainability culture as well as environment. Although thus, the success of this model is greatly influenced by support. policy, skills management community, and engagement active from all over element society. The implications of this study indicate that structured implementation of CBT can be catalyst for development sustainable economy in the region rural.